Internal Tax Regime of WTO: A Clog in the Wheel of Economic Progress of the Developing Countries - Olokooba, Saka Muhammed; Olatoke, Joshua Olukayode; Orubebe, Bibobra B. (NIU Journal of Social Sciences; Vol 3 No 1 (2017): KIU Journal of Social Sciences, Vol. 3 No. 1, March 2017, 2017)
The basic principles of the WTO are built on the foundation of GATT. However, even though those principles are far reaching in importance, their effects on the developed and developing nationâ€™s economy are not equitable. While the principles look novel and economically viable, some of them are damaging to the economic progress of the developing countries. One of such principle is the internal tax regime of the WTO. This paper therefore examines what this principle is all about, how same constitute a clog in the wheel of economic progress of the developing nations as well as solution thereto in form of recommendation.  Key Words: Internal Tax Regime, WTO, Clog, Wheel of Economic Progress, Developing Countries.